EARLY LADINIAN RADIOLARIAN FAUNA FROM THE MONTE SAN GIORGIO (SOUTHERN ALPS, SWITZERLAND): SYSTEMATICS, BIOSTRATIGRAPHY AND PALEO(BIO)GEOGRAPHIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
A well-preserved radiolarian fauna was recovered from the lower part of the San Giorgio Dolomite (Monte San Giorgio, UNESCO WHL, Switzerland), belonging to the Eoprotrachyceras curionii Ammonoid Zone (earliest Ladinian). The depositional environment, consisting of an intraplatform basin with restricted circulation, seemingly resulted in an unusual radiolarian assemblage displaying neglegible percentages and very low diversity of Nassellaria. Seventy-three species have been identified and seven new species have been described: Eptingium danieli n. sp., Eptingium neriae n. sp., Parentactinosphaera eoladinica n. sp., Sepsagon ticinensis n. sp., Sepsagon ? valporinae n. sp., Novamuria wirzi n. sp. and Pessagnollum hexaspinosum n. sp. The taxonomic status of the recovered species has been reassessed and four new genera have been introduced: Bernoulliella gen. n., Eohexastylus gen. n., Ticinosphaera gen. n. and Lahmosphaera gen. n. The new radiolarian assemblages, the first so far described from the Monte San Giorgio, supplement further information to the taxa occurring in the uppermost Ladinocampe multiperforata Radiolarian Zone, as yet poorly defined, also confirming the absence of major changes in the radiolarian fauna across the Anisian/Ladinian boundary. The widespread co-occurrence of taxa doubtlessly testifies to the existence, in early Ladinian times, of open-marine connections between the basin of the Monte San Giorgio and the pelagic “Buchenstein” basins of the central and eastern South-Alpine domain and farther afield across the Tethys.
Keywords: Middle Triassic; Ladinian; Radiolaria; Systematics; Biostratigraphy; Palaeobiogeography; Monte San Giorgio